GÖREREK İŞLEM YAPABİLEN DELTA ROBOTUN TASARIMI VE PERFORMANS KARAKTERİSTİKLERİNİN ARAŞTIRILMASI - ŞANLITÜRK, İSMAİL HAKKI (Fırat Üniveristesi, 2012)
Bu çalışmada görerek işlem yapabilen Delta robotun tasarımının yapılması ve performans karakteristiklerinin araştırılması amaçlanmıştır. Bunun için robotun analitik modeli oluşturulmuş, bu model kullanılarak boyutları optimize edilmiştir. Sonra gerilme analizleri yapılıp istenen şartlarda çalışıp çalışamayacağı belirlenmiştir. Atalet ve yerçekimi kuvvetleri de bu modele etkiletilmiştir. Robotun görme, sınıflandırma ve kontrol yazılımları hazırlandıktan sonra sistemin imalatı yapılmıştır. Son olarak deneysel çalışmalar tamamlanmıştır. Sonuçta görerek işlem yapabilen bir sistem hazırlanmıştır.

In this study, design and investigation of performance characteristics of a vision guided Delta robot has been aimed. The robot?s analytical model has been made, and by using that model in a written optimization script, dimensions of the robot?s elements has been determined. After that, to observe, if the robot have capabilities to suffer given conditions, such as payload and safely running, a stress analysis has been run. Inertial and gravity loads has been applied to the model. After the robot?s vision, classification and control scripts have had written, it has been manufactured. At last, exprimental studies has been completed. As a result, a vision guided system has been designed and manufactured.
Design and investigation of performance characteristics of a vision guided delta robot
Keywords: Makine Mühendisliği